What are the Implications of the Virtualisation of Organisations and the Emergence of Knowledge Management for Management Development? - Burgoyne, John G. (Proceedings of the International Conference on Networked Learning, 2000)
The growing concern with knowledge management and the rapid emergence of virtual organisations are two of the main signs of a revolution in the functioning of organisations, which has profound implications for management development. As firms have become learning organisations knowledge has become the critical resource both as the means of production - state of the an value adding processes, and as the product itself – what firms are selling is knowledge itself or goods and services with a high knowledge value content. Organisational learning is the process by which organisational knowledge is created, renewed and utilised. As part of this process organisations are becoming virtual - new e-commerce firms are created as virtual from scratch, surviving traditional firms are rapidly ’virtualising’ themselves to survive and prosper.